Implementation of the State Research and Technology Policy as a Basis for Management of the Scientific Processes in the Region - Nosachevskaya, Ekaterina (Olsztyn Economic Journal, 2013)
At present, one of the most important lines of state policy is regulation of development of scientific, research and innovative sphere, which is to a large extent reasoned by significant influence of scientific processes on modernization of the present economy. In this connection, issues of effective management of scientific activity both at the federal and at the regional levels become the most important ones. Inter alia, we speak of creation of system for stimulation of interaction of economic entities and scientific organizations with the purpose of development, testing and implementation of advanced Russian technologies into production processes. Individual regions in the framework of their powers frequently use their own stimulation mechanisms, and as a result of implementation thereof, significant differentiation of innovative activity level of Russian enterprises in various subjects of the Russian Federation takes place. Peculiarities of state scientific and engineering policy, preconditions and lines of improvement of state regulation of development of scientific activity in Russia are considered in the article. The author paid special attention to development of recommendations on improvement of this mechanism at the regional level under the current conditions.